Efektivitas Platform Rumah Belajar Sebagai Sumber Belajar Digital di Era Kenormalan Baru - Lubis, Maulana; Johannes, Johannes; Rasyid, Arbanur; Azizan, Nashran (Indonesian Journal of Islamic Elementary Education, 2021)
Today, all sectors, including education, require technology that can facilitate a person's activities, such as obtaining resources for learning. A breakthrough in education is the birth of digital learning resources, which are expected to be a forum to help educators and students obtain information. The breakthrough in question is the Rumah Belajar platform. This study aims to determine the response of educators to the effectiveness of the Rumah Belajar platform. This research is quantitative with a survey approach. The sample used in this study is probability sampling with cluster sampling technique—data collection techniques using a questionnaire. The data analysis technique used the October 2021 version of the STATCAL software. The study results explainedthat out of a total of 129 elementary/MI teachers in Padangsidimpuan City surveyed. A total of 124 (95.98%) teachers stated that the Rumah Belajar platform is a digital learning resource categorized as effective, so it can be used as an information centrein obtaining references according to learning materials in the new normal era.